Women in the church, of disciples to forgotten and subjects of liberation - Polo Medina, Paola (2016)
Along these pages, I make a quick tour around the history of women in the Church to say aloud -among many other voices- what is the reality we have lived and we live women in the Church. This work seeks not only to say the story of suffering and exclusion of women, but also to the current liberation struggles that have broken with women as protagonists and living persons of liberation in history. Also, these lines try to make clear the conviction that the liberation of women is possible and struggle for inclusion and humanization has its horizon and hope in the image of the Kingdom that –from Jesus- that we perceive as willed by God for all human kind.